Metal lithium negative electrode and preparation method thereof
By forming a carbon layer with a roughness of 0.4-0.8nm on the surface of the lithium-containing substrate of the metal lithium negative electrode, the contact problem between metal lithium and air and water is solved, and effective protection of metal lithium and improved battery performance is achieved.
Patent Information
- Application Number
- CN202411443074.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2044-10-16
AI Technical Summary
Due to its high activity, metal lithium is easily reacted with oxygen and water in the air, resulting in a degradation of battery performance. The existing surface protection methods are difficult to effectively isolate the contact between metal lithium and air and water, and the mechanical strength and lithium ion transmission rate are low.
A carbon layer is arranged on the surface of the lithium-containing substrate, and a carbon layer is formed by vacuum carbon plating technology. The roughness of the carbon layer is 0.4-0.8 nm, and the proportion of the sp3 hybrid structure is greater than or equal to 50% to isolate the contact between metal lithium and air and water, and form an intermetallic compound with strong mechanical adhesion.
Effectively isolate the contact between metal lithium and air and water, protect the lithium-containing substrate, inhibit the formation of lithium dendrites, improve the electrochemical performance of the battery, including conductivity and lithium ion transmission rate, and improve the rate performance of the battery.
Smart Images

Figure BDA0005086887060000171 
Figure BDA0005086887060000181 
Figure BDA0005086887060000201
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a metal lithium negative electrode and a preparation method thereof. Background Art
[0002] In recent years, lithium-ion batteries have been widely used in mobile phones, computers and electric vehicles due to their high energy and power density and pollution-free properties.
[0003] Lithium metal is a commonly used negative electrode material for lithium-ion batteries, and it has an extremely high specific capacity. However, due to its high activity, lithium metal is prone to react with oxygen and water in the air when exposed to air for a long time. In the production process of lithium batteries, when using a negative electrode containing a lithium metal layer, it is impossible to complete coating, baking, lamination and other production processes in the air, resulting in reduced battery performance.
[0004] In order to solve the problem that lithium metal is easily oxidized, some studies have used surface protection methods to form a polymer layer on lithium metal to isolate lithium metal from reacting with oxygen and water in the air. However, the mechanical strength and lithium ion transfer rate of the metal lithium negative electrode prepared by this method are low. Summary of the invention
[0005] The purpose of the present invention is to provide a metal lithium negative electrode and a preparation method thereof.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a metallic lithium negative electrode, comprising a lithium-containing substrate and a carbon layer disposed on the surface of the lithium-containing substrate, wherein the surface roughness of the carbon layer is 0.4-0.8 nm, for example, 0.8 nm, 0.6 nm, 0.5 nm or 0.4 nm.
[0008] Preferably, the sp 3 The proportion of the hybrid structure is greater than or equal to 50%, preferably 50% to 80%.
[0009] Preferably, the lithium-containing substrate is selected from any one of a lithium alloy and a lithium foil, wherein the lithium alloy may be, for example, a lithium copper alloy.
[0010] Preferably, the lithium-containing substrate has a thickness of 40 μm to 400 μm.
[0011] Preferably, the thickness of the carbon layer is 1 nm to 200 nm, preferably 1 nm to 100 nm, more preferably 1 nm to 54 nm, and more preferably 10 nm to 54 nm.
[0012] In a second aspect, the present invention provides a method for preparing a metallic lithium negative electrode as described in the first aspect, using a carbon source as a target material and a lithium-containing substrate as a substrate, vacuum-plating carbon on the surface of the lithium-containing substrate to obtain the metallic lithium negative electrode;
[0013] Wherein, during the vacuum carbon plating process, the temperature of the substrate is 1°C to 180°C but does not include 180°C.
[0014] In the present invention, during the vacuum carbon plating process, the carbon source is used as a target to bombard the substrate.
[0015] Preferably, the vacuum carbon plating method is selected from at least one of magnetron sputtering, laser sputtering or arc ion plating.
[0016] Preferably, during the vacuum carbon plating process, the pressure in the vacuum chamber is ≤10 -2 Pa.
[0017] Preferably, the carbon source is selected from at least one of graphite and substances containing carbon nanotubes, or the carbon source is acetylene.
[0018] Preferably, the substance containing carbon nanotubes is carbon nanotubes or a mixture containing carbon nanotubes.
[0019] Preferably, the mixture containing carbon nanotubes is a mixture of carbon nanotubes and polypropylene.
[0020] Preferably, in the mixture of carbon nanotubes and polypropylene, the mass fraction of carbon nanotubes is 15% to 20%.
[0021] As a preferred technical solution of the method of the present invention, in the magnetron sputtering method, the distance between the target material and the substrate is 40 mm to 150 mm.
[0022] Preferably, in the magnetron sputtering method, the working gas is a protective gas, and the flow rate of the working gas is 10 cm 3 / min~30cm 3 / min, and the gas pressure of the working gas is 0.1Pa~1Pa.
[0023] Preferably, in the magnetron sputtering method, the sputtering time is 20 min to 180 min.
[0024] Preferably, in the magnetron sputtering method, the sputtering power is 50W to 300W.
[0025] Preferably, in the magnetron sputtering method, the temperature of the substrate is 50°C to 175°C.
[0026] Preferably, in the magnetron sputtering method, the duty cycle is 20% to 60%.
[0027] Preferably, in the magnetron sputtering method, the substrate bias voltage is -100V to -300V.
[0028] As a preferred technical solution of the method of the present invention, in the laser sputtering method, the distance between the target material and the substrate is 4 cm to 15 cm.
[0029] Preferably, in the laser sputtering method, the frequency of the laser is 4 Hz to 30 Hz.
[0030] Preferably, in the laser sputtering method, the energy density is 0.15 J cm -2 ~1.2J cm -2 .
[0031] Preferably, in the laser sputtering method, the temperature of the substrate is room temperature to 120°C.
[0032] In the present invention, "room temperature" refers to 20°C to 25°C.
[0033] Preferably, in the laser sputtering method, the sputtering time is 1 min to 120 min.
[0034] Preferably, in the laser sputtering method, the angle between the laser incident direction and the target surface is 40° to 60°.
[0035] Preferably, in the laser sputtering method, the rotation speed of the target is 0.5 rpm to 15 rpm.
[0036] Preferably, in the laser sputtering method, the substrate bias voltage is -100V to -300V.
[0037] Preferably, in the laser sputtering method, the partial pressure of the inert gas is maintained at 0.1Pa to 10Pa.
[0038] As a preferred technical solution of the method of the present invention, in the arc ion plating method, when the carbon source is selected from at least one of graphite and a substance containing carbon nanotubes, at least one of the following conditions is met:
[0039] (a) The arc source current is 10A to 100A.
[0040] (b) The substrate bias is -200V to -750V.
[0041] (c) The duty cycle is 10% to 70%.
[0042] (d) The working voltage is 20V~50V.
[0043] (e) The distance between the target and the substrate is 10 cm to 30 cm.
[0044] (f) The argon gas flow rate is 10 sccm to 110 sccm.
[0045] (g) During the arc ion plating process, the temperature of the substrate is between room temperature and 120°C.
[0046] As a preferred technical solution of the method of the present invention, in the arc ion plating method, when the carbon source is acetylene, at least one of the following conditions is met:
[0047] (h) The flow rate of acetylene gas is 30 sccm to 200 sccm.
[0048] (i) The evaporation time is 20 min to 100 min.
[0049] Compared with the prior art, the present invention has the following beneficial effects:
[0050] (1) The present invention provides a metal lithium negative electrode, wherein a carbon layer is disposed on the surface of a lithium-containing substrate, which can not only isolate the metal lithium from contact with air and water, protect the lithium-containing substrate, and inhibit lithium dendrites, but also form an intermetallic compound between the carbon layer and the lithium-containing substrate, with strong mechanical adhesion, and the carbon layer is not easy to fall off. The metal lithium negative electrode also has good electrical conductivity and high lithium ion transmission rate, thereby improving the electrochemical performance of the battery. Moreover, the appropriate roughness of the carbon layer can effectively reduce the interface impedance between the metal lithium negative electrode and the electrolyte, and improve the rate performance of the lithium metal battery.
[0051] (2) The present invention controls the sp 3 The proportion of hybrid structure can improve the density and uniformity of the carbon layer, thereby better protecting the metallic lithium negative electrode and inhibiting the formation of lithium dendrites.
[0052] (3) The method of the present invention is easy to operate and can be applied in large-scale production. DETAILED DESCRIPTION
[0053] The technical solution of the present invention is further illustrated below through specific implementation methods.
[0054] One embodiment of the present invention provides a metallic lithium negative electrode, which includes a lithium-containing substrate and a carbon layer arranged on the surface of the lithium-containing substrate, and the roughness of the surface of the carbon layer is 0.4-0.8nm, for example, it can be 0.8nm, 0.6nm, 0.5nm or 0.4nm.
[0055] In one embodiment, the present invention provides a metal lithium negative electrode, wherein a carbon layer is provided on the surface of a lithium-containing substrate, which can not only isolate the metal lithium from contact with air and water, protect the lithium-containing substrate, and inhibit lithium dendrites, but also form an intermetallic compound between the carbon layer and the lithium-containing substrate, with strong mechanical adhesion, and the carbon layer is not easy to fall off. The metal lithium negative electrode also has good conductivity and high lithium ion transmission rate, thereby improving the electrochemical performance of the battery. Among them, the appropriate roughness can effectively reduce the interface impedance between the metal lithium negative electrode and the electrolyte, and improve the rate performance of the lithium metal battery.
[0056] In one embodiment, the sp 3 The proportion of hybrid structures is greater than or equal to 50%, for example, it can be 50%, 52%, 55%, 58%, 60%, 63%, 66%, 68%, 70%, 72%, 74%, 76%, 78%, 80%, 83%, 85% or 88%, etc., preferably 50% to 80%.
[0057] Generally speaking, the structure of carbon atoms in the carbon layer is divided into sp 2 Hybrid structure and sp 3 Hybrid structure, regulating the composition of carbon atoms in these two structures is the main factor affecting the performance of the carbon layer. 2 The hybrid structure is more similar to graphite, and the carbon film at this time shows better electrochemical performance. However, the present invention is different from this. The present invention uses a carbon layer to protect the lithium-containing substrate. The sp 3 When the proportion of the hybrid structure is greater than or equal to 50%, the carbon layer is denser and more uniform, which can effectively protect the metallic lithium negative electrode and inhibit the formation of lithium dendrites.
[0058] In one embodiment, the lithium-containing substrate is selected from any one of a lithium alloy and a lithium foil, wherein the lithium alloy may be, for example, a lithium copper alloy.
[0059] In one embodiment, the lithium-copper alloy may be a foil or substrate made of lithium-copper alloy, or may be a composite foil or composite substrate formed by a lithium sheet and a copper sheet.
[0060] In one embodiment, the thickness of the lithium-containing substrate is 40 μm to 400 μm, for example, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 185 μm, 200 μm, 210 μm, 220 μm, 240 μm, 260 μm, 280 μm, 300 μm, 320 μm, 340 μm, 360 μm, 380 μm or 400 μm, etc.
[0061] In one embodiment, the thickness of the carbon layer is 1nm to 200nm, for example, 1nm, 3nm, 5nm, 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm or 200nm, etc., preferably 1nm to 100nm, more preferably 1nm to 54nm, and more preferably 10nm to 54nm. In the present invention, the thickness of the carbon layer is relatively thin, which can protect the lithium-containing substrate while ensuring that the metal lithium negative electrode has a high energy density. At the same time, the thickness of the carbon layer will affect the modification effect of the lithium-containing substrate. If the carbon layer is too thin, the protective effect of the carbon layer will be weakened, and it will be difficult to ensure that the metal lithium is not oxidized; if the carbon layer is too thick, not only will the energy density of the lithium metal negative electrode be reduced, but it will also be more likely to cause the carbon layer to fall off, and the mechanical properties will deteriorate.
[0062] In another embodiment, the present invention provides a method for preparing the above-mentioned metal lithium negative electrode, using a carbon source as a target material and a lithium-containing substrate as a substrate, vacuum-plating carbon on the surface of the lithium-containing substrate to obtain the metal lithium negative electrode;
[0063] Wherein, during the vacuum carbon plating process, the temperature of the substrate is 1°C to 180°C and does not include 180°C, for example, 5°C, 10°C, 15°C, 20°C, 25°C, 30°C, 40°C, 45°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C or 175°C, etc.
[0064] In one embodiment of the present invention, during the vacuum carbon plating process, the carbon source is used as a target to bombard the substrate.
[0065] The method provided by one embodiment of the present invention uses a carbon source as a target to bombard a lithium-containing substrate to achieve surface modification, and introduces a carbon layer on the surface of the lithium-containing substrate, which can not only isolate the metallic lithium from contact with air and water, protect the lithium-containing substrate, and inhibit lithium dendrites, but also the prepared modified metallic lithium negative electrode also has good conductivity and high lithium ion transmission rate, thereby improving the electrochemical performance of the battery. It should be noted that during the formation of the carbon layer, the temperature of the lithium-containing substrate should be less than 180°C, otherwise it will affect the morphology of the metallic lithium, the introduction and uniformity of the carbon layer, and thus make it impossible to form an effective carbon layer on the lithium-containing substrate, and even more impossible to inhibit lithium dendrites and improve electrochemical performance.
[0066] In one embodiment, the vacuum carbon plating method is selected from at least one of magnetron sputtering, laser sputtering or arc ion plating.
[0067] In one embodiment, during the vacuum carbon plating process, the pressure in the vacuum chamber is ≤10 -2 Pa.
[0068] In one embodiment, the carbon source is selected from at least one of graphite and a substance containing carbon nanotubes, or the carbon source is acetylene.
[0069] In one embodiment, the substance containing carbon nanotubes is carbon nanotubes or a mixture containing carbon nanotubes.
[0070] In one embodiment, the mixture containing carbon nanotubes is a mixture of carbon nanotubes and polypropylene.
[0071] In one embodiment, in the mixture of carbon nanotubes and polypropylene, the mass fraction of carbon nanotubes is 15% to 20%, for example, 15%, 16%, 16.5%, 17%, 18%, 18.5%, 19% or 20%.
[0072] In one embodiment, in the magnetron sputtering method, the distance between the target and the substrate is 40 mm to 150 mm, for example, 40 mm, 50 mm, 60 mm, 70 mm, 80 mm, 90 mm, 100 mm, 110 mm, 120 mm, 130 mm, 140 mm or 150 mm.
[0073] In one embodiment, in the magnetron sputtering method, the working gas is a protective gas, and the flow rate of the working gas is 10 cm 3 / min~30cm 3 / min, and the gas pressure of the working gas is 0.1Pa-1Pa, for example, 0.1Pa, 0.3Pa, 0.5Pa, 0.6Pa, 0.8Pa or 1Pa.
[0074] In one embodiment, in the magnetron sputtering method, the sputtering time is 20 min to 180 min, for example, 20 min, 25 min, 30 min, 35 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min, 120 min, 130 min, 140 min, 150 min, 160 min, 170 min or 180 min, etc.
[0075] In one embodiment, in the magnetron sputtering method, the sputtering power is 50W to 300W, such as 50W, 60W, 70W, 80W, 90W, 100W, 110W, 120W, 140W, 160W, 180W, 200W, 220W, 240W, 260W, 280W or 300W. The sputtering power affects the energy of the carbon ions. As the sputtering power increases, the sp 3 The increase in the proportion of carbon atoms in the hybrid structure is conducive to the formation of a dense and uniform carbon film, but the sputtering power should not be too high, because under too high a sputtering power, the sp 3 The proportion of carbon atoms in the hybrid structure decreases, which reduces the density and uniformity of the carbon film.
[0076] In one embodiment, in the magnetron sputtering method, the temperature of the substrate is 50° C. to 175° C. The temperature of the substrate will affect the sp 2 Hybrid structure and sp 3 The proportion of hybrid structure. If the substrate temperature is too low, the sp 3 The hybridization ratio will increase the surface roughness of the carbon layer and affect the morphology; if the substrate temperature is too high, the lithium metal will melt.
[0077] In one embodiment, in the magnetron sputtering method, the duty cycle is 20% to 60%, such as 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55% or 60%. The larger the duty cycle, the higher the pulse frequency in the same time, and the higher the frequency of carbon ions excited by the target material bombarding the substrate. A higher duty cycle is conducive to the formation of sp 3 The increase in the proportion of the hybrid structure generates a denser film structure, which effectively protects the metallic lithium. However, too high a duty cycle will make sp 3 The proportion of hybrid structures decreases.
[0078] In one embodiment, in the magnetron sputtering method, the substrate bias is -100V to -300V. In the magnetron sputtering method, the substrate bias has an important influence on the structure and properties of the carbon layer. The substrate bias can not only affect the density of the carbon layer, but also affect the roughness of the carbon layer and the thickness of the carbon layer. Specifically, on the first aspect, as the substrate bias increases, the density of the carbon layer first increases and then decreases. The reason is that when the substrate bias is small, the energy of carbon ions is small, which is not enough to be injected into the film layer or migrate to the surrounding area, and is only adsorbed on the surface of the film layer; when the substrate bias increases, the energy increases, and it can be injected into the film layer or migrate to the surrounding area. The carbon ions are injected into the sub-surface layer to form a stable sp 3Hybrid structure, density is improved. As the substrate bias continues to increase, the bombardment energy on the substrate is too large, and the originally formed dense structure is destroyed, resulting in a decrease in density. On the second hand, with the increase of the substrate bias, the surface roughness of the carbon layer shows a trend of first decreasing and then increasing. The reason is: appropriate substrate bias will make the energized ions have higher energy, realize surface ion migration and diffusion to remove large particles, and reduce the surface roughness, while insufficient or excessive energy will increase the surface roughness. On the third hand, with the increase of the substrate bias, the thickness of the film layer shows a trend of first increasing and then decreasing. When the substrate bias is controlled in the range of -100V to -300V, higher density, lower roughness and suitable thickness can be taken into account.
[0079] In one embodiment, in the laser sputtering method, the distance between the target and the substrate is 4 cm to 15 cm, such as 4 cm, 5 cm, 6 cm, 7 cm, 8 cm, 9 cm, 10 cm, 11 cm, 13 cm or 15 cm, etc. The distance between the target and the substrate affects the deposition rate, but has little effect on the carbon layer structure.
[0080] In one embodiment, in the laser sputtering method, the frequency of the laser is 4 Hz to 30 Hz, such as 4 Hz, 6 Hz, 8 Hz, 10 Hz, 12 Hz, 15 Hz, 17 Hz, 20 Hz, 22 Hz, 24 Hz, 25 Hz, 28 Hz or 30 Hz. Reducing the wavelength, increasing the frequency of the laser, and increasing the energy are generally beneficial to the carbon atom sp 3 When the laser frequency is too low or too high, it will cause the sp 3 The structure is reduced, thereby reducing the density and uniformity of the carbon film, thereby reducing the protective effect of the carbon film on metallic lithium.
[0081] In one embodiment, in the laser sputtering method, the energy density is 0.15 J cm -2 ~1.2J cm -2 , for example 0.15 J cm -2 , 0.2J cm -2 , 0.25J cm -2 , 0.3J cm -2 , 0.35J cm -2 , 0.4J cm -2 , 0.45J cm -2 , 0.5J cm -2 , 0.55J cm -2 , 0.6J cm -2 , 0.65J cm -2 , 0.7J cm -2 , 0.8J cm -2, 0.9J cm -2 or 1.0 J cm -2 、1.1Jcm -2 or 1.2 J cm -2 If the sputtering energy is too small, the film thickness will be reduced. 3 As the proportion of hybridization decreases, the density of the film decreases, and the protective effect on metallic lithium will decrease.
[0082] In one embodiment, in the laser sputtering method, the temperature of the substrate is room temperature to 120° C. In the laser sputtering method, a lower substrate temperature is not conducive to the sp 3 The formation of hybrid structure, although with the increase of temperature, it is favorable for sp 3 However, too high a substrate temperature is not conducive to the formation of sp 3 The formation of hybrid structure reduces the density and uniformity of the film layer.
[0083] In the embodiment of the present invention, "room temperature" refers to 20°C to 25°C, for example, it can be 20°C, 22°C, 23°C, 24°C or 25°C.
[0084] In one embodiment, in the laser sputtering method, the sputtering time is 1 min to 120 min, for example, 1 min, 3 min, 6 min, 8 min, 10 min, 15 min, 20 min, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min or 120 min, etc.
[0085] In one embodiment, in the laser sputtering method, the angle between the laser incident direction and the target surface is 40° to 60°, such as 40°, 45°, 50°, 55° or 60°. 2 The structural proportion will increase, thereby reducing the density and uniformity of the carbon film material.
[0086] In one embodiment, in the laser sputtering method, the rotation speed of the target is 0.5rpm to 15rpm, for example, 0.5rpm, 1rpm, 2rpm, 3rpm, 4rpm, 5rpm, 7rpm, 8rpm, 10rpm, 11rpm, 12rpm, 13rpm, 14rpm or 15rpm, etc.
[0087] In one embodiment, in the laser sputtering method, the substrate bias voltage is -100 V to -300 V. Too low or too high substrate bias voltage will reduce sp 3 The proportion of hybrid structure affects the density and uniformity of the film.
[0088] In one embodiment, in the laser sputtering method, the inert gas partial pressure is maintained at 0.1Pa to 10Pa, such as 0.1Pa, 0.3Pa, 0.5Pa, 0.6Pa, 0.8Pa, 1Pa, 2Pa, 3Pa, 4Pa, 5Pa, 6Pa, 7Pa, 8Pa or 10Pa. Inert gas can hinder the formation of carbon particles and reduce their kinetic energy, so a relatively large inert gas pressure is not conducive to the sp 3 The formation of hybrid structures.
[0089] In one embodiment, in the arc ion plating method, when the carbon source is selected from at least one of graphite and a substance containing carbon nanotubes, at least one of the following conditions is satisfied:
[0090] (a) The arc source current is 10A to 100A, for example, 10A, 15A, 20A, 25A, 30A, 35A, 40A, 45A, 50A, 55A, 60A, 65A, 70A, 75A, 80A, 90A or 100A, etc. Within this preferred range, the formation of the sp3 hybrid structure is more favorable, thereby improving the compactness and uniformity of the carbon layer.
[0091] (b) The substrate bias is -200V to -750V, such as -200V, -250V, -300V, -350V, -400V, -450V, -500V, -550V, -600V, -650V, -700V or -750V. The effect of substrate bias on the structure of the carbon layer is relatively complex. Generally speaking, the sp 3 The proportion of hybrid structure increases first and then decreases with the increase of substrate bias. Within the above preferred range, it is conducive to the formation of a higher proportion of sp 3 Hybrid structure.
[0092] (c) The duty ratio is 10% to 70%, such as 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65% or 70%. A higher duty ratio is conducive to the formation of sp atoms in the carbon layer. 3 Hybridization, when the duty cycle is too low or too high, will cause sp 3 The proportion of hybrid structure decreases, and the density and uniformity of the carbon film decrease.
[0093] (d) The operating voltage is 20V to 50V, for example, 20V, 25V, 30V, 35V, 40V, 45V or 50V.
[0094] (e) The distance between the target and the substrate is 10 cm to 30 cm, for example, 10 cm, 12 cm, 15 cm, 18 cm, 20 cm, 23 cm, 26 cm, 28 cm or 30 cm.
[0095] (f) The argon gas flow rate is 10 sccm to 110 sccm, for example, 10 sccm, 20 sccm, 30 sccm, 40 sccm, 50 sccm, 60 sccm, 70 sccm, 80 sccm, 90 sccm, 100 sccm or 110 sccm.
[0096] (g) During the arc ion plating process, the substrate temperature is room temperature to 120°C. Properly lowering the substrate temperature will be beneficial to the sp 3 The formation of hybrid structure, at the same time, considering the properties of metallic lithium, the substrate temperature should not be too high.
[0097] In one embodiment, in the arc ion plating method, when the carbon source is acetylene, at least one of the following conditions is met:
[0098] (h) The flow rate of acetylene gas is 30 sccm to 200 sccm, for example, 30 sccm, 40 sccm, 50 sccm, 60 sccm, 70 sccm, 80 sccm, 90 sccm, 100 sccm, 110 sccm, 120 sccm, 130 sccm, 140 sccm, 150 sccm, 160 sccm, 180 sccm or 200 sccm, etc.
[0099] (i) The evaporation time is 20 min to 100 min, for example, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 60 min, 70 min, 80 min, 90 min or 100 min.
[0100] When acetylene is used as the carbon source, the flow rate of acetylene gas and the evaporation time are the main factors affecting the carbon layer structure. In order to form more sp 3 Hybrid structure, in order to improve the density and uniformity of the carbon layer, the flow rate of acetylene gas should not be too slow, and the deposition time should not be too long. The preferred acetylene gas flow rate is 100 sccm-180 sccm, and the preferred deposition time range is 30 min-60 min.
[0101] Example 1
[0102] This embodiment provides a method for preparing a metallic lithium negative electrode, comprising the following steps:
[0103] (1) Pretreatment: First, a lithium-copper alloy with a thickness of 250 μm (wherein the lithium-copper alloy is composed of a copper foil and lithium sheets arranged on both sides of the copper foil, the copper foil is 5 μm thick, and the thickness of the lithium sheets on both sides of the copper foil is 100 μm respectively) is immersed in acetone for a period of time, and then placed in a drying room to dry naturally (dew point ≤ 50°C).
[0104] (2) Magnetron sputtering: The dried lithium-copper alloy was placed in the chamber of the magnetron sputtering equipment. A graphite sheet with a purity of 99.9% was used as the target material and the lithium-copper alloy was used as the substrate. A molecular pump was used to control the vacuum degree at 1×10 -3 Pa, the target-substrate distance (the distance between the target and the lithium-copper alloy) is fixed at 50 mm, and the working gas is argon with an argon flow rate of 20 cm 3 / min, argon partial pressure of 0.9Pa, duty cycle of 30%, sputtering power of 100W, sputtering time of 30min, substrate temperature of 50℃, carbon layer formed, after sputtering, the surface modified copper-lithium alloy substrate was taken out, the thickness of carbon layer was 50nm, and the sp 3 The hybrid structure accounts for 50.8%, that is, a metallic lithium negative electrode is obtained.
[0105] Example 2
[0106] Different from Example 1, the temperature of the substrate was adjusted to 70°C.
[0107] Example 3
[0108] Different from Example 1, the temperature of the substrate was adjusted to 90°C.
[0109] Example 4
[0110] Different from Example 1, the temperature of the substrate was adjusted to 110°C.
[0111] Example 5
[0112] Different from Example 1, the temperature of the substrate was adjusted to 130°C.
[0113] Example 6
[0114] Different from Example 1, the temperature of the substrate was adjusted to 170°C.
[0115] Example 7
[0116] The difference from the first embodiment is that the duty cycle is adjusted to 40%.
[0117] Example 8
[0118] The difference from Example 1 is that the duty cycle is adjusted to 50%. Example 9
[0119] The difference from the first embodiment is that the duty cycle is adjusted to 20%.
[0120] Example 10
[0121] The difference from the first embodiment is that the duty cycle is adjusted to 60%.
[0122] Embodiment 11
[0123] This embodiment provides a method for preparing a metallic lithium negative electrode, comprising the following steps:
[0124] (1) Pretreatment: First, a lithium foil with a thickness of 200 μm was immersed in acetone for a period of time, and then placed in a drying room to dry naturally (dew point ≤ 50°C).
[0125] (2) Laser sputtering: A carbon nanotube / polypropylene mixture (wherein the mass fraction of carbon nanotubes is 15%) is used as a target material, and a dried lithium foil is used as a substrate. The target material and the substrate are placed in a vacuum chamber, and the distance between the target material and the substrate is adjusted to 8 cm. The vacuum degree of the chamber is pumped to less than 1×10 -3 Pa, the temperature of the substrate was raised to 60 °C, the frequency of the laser was 20 Hz, and the energy density was set to 0.4 J cm -2 , the sputtering time was 80 min, the angle between the laser and the target was 60°, the target rotation speed was 10 rpm, the inert gas partial pressure was maintained at 7 Pa, a carbon layer was formed, the thickness of the carbon layer was 59 nm, and a metallic lithium negative electrode was obtained.
[0126] Example 12
[0127] Different from Example 10, the temperature of the substrate was adjusted to 80°C.
[0128] Example 13
[0129] Different from Example 10, the temperature of the substrate was adjusted to 100°C.
[0130] Embodiment 14
[0131] Different from Example 10, the temperature of the substrate was adjusted to 40°C.
[0132] Embodiment 15
[0133] Different from Example 10, the temperature of the substrate was adjusted to 120°C.
[0134] Example 16
[0135] Different from Example 10, the energy density was adjusted to 0.2 J cm -2 .
[0136] Embodiment 17
[0137] Different from Example 10, the energy density was adjusted to 0.6 J cm -2 .
[0138] Embodiment 18
[0139] Different from Example 10, the energy density was adjusted to 0.8 J cm -2 .
[0140] Embodiment 19
[0141] Different from Example 10, the energy density was adjusted to 1.0 J cm -2 .
[0142] Embodiment 20
[0143] Different from Example 10, the energy density was adjusted to 1.2 J cm -2 .
[0144] Embodiment 21
[0145] (1) Pretreatment: First, a lithium-copper alloy with a thickness of 250 μm (wherein the lithium-copper alloy is composed of a copper foil and lithium sheets arranged on both sides of the copper foil, the copper foil is 5 μm thick, and the thickness of the lithium sheets on both sides of the copper foil is 100 μm respectively) is immersed in acetone for a period of time, and then placed in a drying room to dry naturally (dew point ≤ 50°C).
[0146] (2) Arc ion plating method: Using graphite with a purity of 99.9% as the target material and the dried lithium-copper alloy as the substrate, the arc ion plating equipment chamber is first evacuated to 1×10 -3 Pa, the distance between the fixed target and the substrate is 200mm, the argon partial pressure is 0.1Pa, the arc source current is 20A, the substrate bias is -200V, the duty cycle is adjusted to 20%, the working voltage is 30V, the coating time is 20min, the substrate temperature is adjusted to 50℃, and the negative electrode sheet is taken out after the coating is completed.
[0147] Embodiment 22
[0148] Different from Example 18, the temperature of the substrate is adjusted to 60°C.
[0149] Embodiment 23
[0150] Different from Example 18, the temperature of the substrate was adjusted to 70°C.
[0151] Embodiment 24
[0152] Different from Example 18, the temperature of the substrate is adjusted to 80°C.
[0153] Embodiment 25
[0154] Different from Example 18, the temperature of the substrate was adjusted to 90°C.
[0155] Embodiment 26
[0156] Different from Example 18, the temperature of the substrate is adjusted to 100°C.
[0157] Embodiment 27
[0158] Different from Example 18, the temperature of the substrate is adjusted to 120°C.
[0159] Embodiment 28
[0160] Different from Example 18, the duty cycle is adjusted to 30%.
[0161] Embodiment 29
[0162] Different from Example 18, the duty cycle is adjusted to 40%.
[0163] Embodiment 30
[0164] The difference from Example 18 is that the duty cycle is adjusted to 50%.
[0165] Embodiment 31
[0166] The difference from Example 18 is that the duty cycle is adjusted to 60%.
[0167] Embodiment 32
[0168] Different from Example 18, the duty cycle is adjusted to 70%.
[0169] Comparative Example 1
[0170] Different from Example 1, the temperature of the substrate is above 200°C.
[0171] When the temperature is above 180°C, the metallic lithium melts and film deposition cannot be performed.
[0172] Comparative Example 2
[0173] Different from Example 1, a lithium-copper alloy is directly used as the metallic lithium negative electrode, and no carbon layer is formed on its surface.
[0174] Comparative Example 3
[0175] The difference from the first embodiment is that the duty cycle is adjusted to 10%.
[0176] Comparative Example 4
[0177] Different from Example 10, the sputtering energy was adjusted to 0.1 J cm -2 .
[0178] The structural parameters of the metal lithium negative electrodes of Examples 1-27 and Comparative Examples 1-9 were tested in the same manner as shown in Table 1. The roughness of the carbon layer was tested by using a Taylor Hobson profilometer; the sp 3 The test method for the proportion of hybrid structure is: using Raman spectroscopy to test, the asymmetric peak of the sample can be divided into two peaks using Gaussian function, one is the D peak, which is generated by the T2g symmetric vibration motion mode, proving that there is sp 3 The existence of hybrid structure, and the G peak is generated by the D2g symmetric vibration motion mode, proving the existence of sp 2 The existence of hybrid structure, by comparing the peak intensities of the two peaks, the sp 3 The proportion of hybrid structures.
[0179] Table 1
[0180]
[0181]
[0182] Note: Comparative Example 2 does not contain a carbon layer, so there is no corresponding data in the table and it is replaced by “——”.
[0183] It can be seen from Examples 1-32 that magnetron sputtering, laser sputtering or arc ion plating can all achieve a certain roughness and a certain ratio sp 3 Hybridized carbon layer. In Comparative Example 1, the substrate temperature is too high, which will cause the lithium metal to melt. In Comparative Example 3, the duty cycle is too small, resulting in the sp 3 The hybridization ratio is too low, which is not conducive to the compactness of the film. 3 The ratio of hybridization is too low and the roughness is small.
[0184] At the same time, by comparing Example 1 with Example 10, it can be seen that in the magnetron sputtering method, when the duty cycle is 60%, compared with the duty cycle of 30% in Example 1, the sp 3 The proportion of the hybrid structure is 50%, and the energy consumed is greater. Moreover, compared with the duty cycle of 50% in Example 8, sp 3 The hybrid structure decreases instead, which shows that the higher the duty cycle is, the better.
[0185] By comparing Example 10 with Example 15, it can be seen that in the laser sputtering method, when the substrate temperature is 120°C, compared with 60°C in Example 10, the sp 3 The proportion of hybrid structure is higher, and the energy consumed is greater. Moreover, compared with 100℃ in Example 13, sp3 The hybrid structure decreases instead, which shows that the higher the substrate temperature is, the better.
[0186] By comparing Example 10 with Example 20, it can be seen that in the laser sputtering method, the sputtering energy is 1.2 Jcm -2 Compared with 0.4 J cm -2 , can improve sp to a certain extent 3 The proportion of hybrid structure is higher, and the energy consumed is greater. At the same time, compared with 0.6-1.0 J cm -2 , sp 3 The hybrid structure decreases instead, which shows that the higher the sputtering energy is, the better.
[0187] By comparing Example 18 with Example 27, it can be seen that in the arc ion plating method, when the substrate temperature is 120°C, compared with 50°C in Example 18, the sp 3 At the same time, compared with 80-100℃ in Examples 24-26, sp 3 The hybrid structure decreases instead, which shows that the higher the substrate temperature is, the better.
[0188] By comparing Example 18 with Example 32, it can be seen that in the arc ion plating method, when the duty cycle is 70%, compared with the duty cycle of 20% in Example 1, the sp 3 The proportion of hybrid structure is higher, and the energy consumed is greater. At the same time, compared with 40-60% of Examples 29-31, sp 3 The hybrid structure decreases instead, which shows that the higher the duty cycle is, the better.
[0189] Performance Test:
[0190] (I) Metal lithium batteries were assembled using the metal lithium negative electrodes of Examples 1-32 and Comparative Examples 1-4, and the electrochemical performance of the batteries was tested:
[0191] The above-mentioned metal lithium negative electrode is used as the negative electrode, and the ternary material LiNi 0.8 Co 0.1 Mn 0.1O2 is a ternary active material for making the positive electrode. The production process of the positive electrode material is as follows: the mass proportion of the ternary active material is 95%, the mass proportion of the binder PVDF is 5%, the mass proportion of the conductive agent Super P is 5%, and the dispersant is nitrogen methyl pyrrolidone (NMP). First, the NMP solution of PVDF (mass fraction is 6%) is placed in a stirrer, and then the conductive agent of the corresponding proportion is added. After stirring for a period of time, the ternary active material is added, and then a certain amount of dispersant NMP is added to maintain the solid content of the whole system at 60%. The positive electrode sheet is prepared by coating with a coating machine, and the surface density of the positive electrode sheet is 35 mg / cm 2 , assembled into several soft-pack batteries, and tested their cycle and rate performance.
[0192] Among them, the test conditions for the cycle performance are: 1C charge and discharge at room temperature, and calculation of the capacity and energy retention rate after 200 cycles.
[0193] The test conditions for rate performance are: at room temperature, charge and discharge tests are performed at 0.5C, 1C, 3C, and 5C conditions, and the capacity under different rate performance is calculated. By comparing the capacity under 1C, 3C, and 5C conditions with the capacity under 0.5C conditions, the rate performance can be evaluated. The results are shown in Table 2.
[0194] Table 2
[0195]
[0196]
[0197]
[0198] In summary, the present invention provides a carbon layer on the surface of the substrate, which can not only isolate the metallic lithium from contact with air and water, protect the substrate and inhibit lithium dendrites, but also form an intermetallic compound between the carbon layer and the substrate, have strong mechanical adhesion, and the carbon layer is not easy to fall off. The prepared modified metallic lithium negative electrode also has good conductivity and high lithium ion transfer rate, thereby improving the electrochemical performance of the battery.
[0199] The comparison between the embodiment and comparative examples 1 and 2 illustrates that the carbon layer can be effectively formed at a temperature below 200° C., which protects the metallic lithium and prevents the metallic lithium from being oxidized, and has good lithium ion transport performance.
[0200] By comparing Example 1 with Comparative Example 3, and by comparing Example 10 with Comparative Example 4, it can be seen that the sp 3 The hybridization ratio is too low and the roughness is small, which is not conducive to the improvement of electrochemical performance.
[0201] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A metallic lithium negative electrode, characterized in that: The metal lithium negative electrode comprises a lithium-containing substrate and a carbon layer arranged on the surface of the lithium-containing substrate, and the surface roughness of the carbon layer is 0.4-0.8 nm.
2. The metallic lithium negative electrode according to claim 1, characterized in that: The sp 3 The proportion of the hybrid structure is greater than or equal to 50%, preferably 50% to 80%.
3. The metallic lithium negative electrode according to claim 1 or 2, characterized in that: The lithium-containing substrate is selected from any one of lithium alloy and lithium foil; Preferably, the lithium-containing substrate has a thickness of 40 μm to 400 μm.
4. The metal lithium negative electrode according to any one of claims 1 to 3, characterized in that The thickness of the carbon layer is 1 nm to 200 nm, preferably 1 nm to 100 nm, more preferably 1 nm to 54 nm, and even more preferably 10 nm to 54 nm.
5. A method for preparing a metallic lithium negative electrode as claimed in any one of claims 1 to 4, characterized in that: Using a carbon source as a target material and a lithium-containing substrate as a base, vacuum-plating carbon on the surface of the lithium-containing substrate to obtain the metallic lithium negative electrode; Wherein, during the vacuum carbon plating process, the temperature of the substrate is 1°C to 180°C but does not include 180°C.
6. The preparation method according to claim 5, characterized in that: The vacuum carbon plating method is selected from at least one of magnetron sputtering, laser sputtering or arc ion plating; Preferably, during the vacuum carbon plating process, the pressure in the vacuum chamber is ≤10 -2 Pa; Preferably, the carbon source is selected from at least one of graphite or a substance containing carbon nanotubes, or the carbon source is acetylene; Preferably, the substance containing carbon nanotubes is carbon nanotubes or a mixture containing carbon nanotubes; Preferably, the mixture containing carbon nanotubes is a mixture of carbon nanotubes and polypropylene; Preferably, in the mixture of carbon nanotubes and polypropylene, the mass fraction of carbon nanotubes is 15% to 20%.
7. The method according to claim 6, characterized in that In the magnetron sputtering method, the distance between the target and the substrate is 40 mm to 150 mm; Preferably, in the magnetron sputtering method, the working gas is a protective gas, and the flow rate of the working gas is 10 cm 3 / min~30cm 3 / min, the pressure of the working gas is 0.1Pa~1Pa; Preferably, in the magnetron sputtering method, the sputtering time is 20 min to 180 min; Preferably, in the magnetron sputtering method, the sputtering power is 50W to 300W; Preferably, in the magnetron sputtering method, the temperature of the substrate is 50°C to 175°C; Preferably, in the magnetron sputtering method, the duty cycle is 20% to 60%; Preferably, in the magnetron sputtering method, the substrate bias voltage is -100V to -300V.
8. The method according to claim 6, characterized in that In the laser sputtering method, the distance between the target and the substrate is 4 cm to 15 cm; Preferably, in the laser sputtering method, the frequency of the laser is 4 Hz to 30 Hz; Preferably, in the laser sputtering method, the energy density is 0.15 Jcm -2 ~1.2Jcm -2 ; Preferably, in the laser sputtering method, the temperature of the substrate is room temperature to 120°C; Preferably, in the laser sputtering method, the sputtering time is 1 min to 120 min; Preferably, in the laser sputtering method, the angle between the laser incident direction and the target surface is 40° to 60°; Preferably, in the laser sputtering method, the rotation speed of the target is 0.5 rpm to 15 rpm; Preferably, in the laser sputtering method, the substrate bias voltage is -100V to -300V; Preferably, in the laser sputtering method, the partial pressure of the inert gas is maintained at 0.1Pa to 10Pa.
9. The method according to claim 6, characterized in that In the arc ion plating method, when the carbon source is selected from at least one of graphite and a substance containing carbon nanotubes, at least one of the following conditions is met: (a) Arc source current is 10A~100A; (b) substrate bias is -200V to -750V; (c) Duty cycle is 10% to 70%; (d) The working voltage is 20V to 50V; (e) the distance between the target and the substrate is 10 cm to 30 cm; (f) The flow rate of the protective gas is 10 sccm to 110 sccm; (g) During the arc ion plating process, the temperature of the substrate is between room temperature and 120°C.
10. The method according to claim 6 or 9, characterized in that: In the arc ion plating method, when the carbon source is acetylene, at least one of the following conditions is met: (h) the flow rate of acetylene gas is 30 sccm to 200 sccm; (i) The evaporation time is 20 min to 100 min.
Citation Information
Patent Citations
Electrode and electrochemical measurement system
CN113574370A
Lithium metal negative electrode, lithium metal battery, preparation method of lithium metal negative electrode and lithium metal battery and method for inhibiting lithium dendrites
CN114388746A
Carbon-coated current collector and preparation method thereof
CN117219780A
Lithium electrode and lithium secondary battery including same
CN209329034U
Method and robot for measuring vessel berthing speed
KR1020250065471A